Socially marked vocabulary in the literary texts (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article is devoted to the peculiarities of functioning of socially marked lexemes in the modern literary texts. Stylistic functions and expressive potential of social dialecticisms used  in the modern Ukrainian prose texts are described.
Keywords: socially marked vocabulary; social dialecticisms; modern Ukrainian prose